Finland : Financial sector Assessment Program: Technical Note-Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Finland in the area of macroprudential policy framework. The Finnish authorities regularly coordinate and collaborate with international bodies on macroprudential policy. Several macroprudential instruments were formally introduced in the legislation and activated recently. The 2014 Act on Credit Institutions implements macroprudential instruments, including those set out in the European Capital Requirement Directive. Despite the important progress made, there are some improvements that should be considered. The macroprudential policy toolkit should be expanded. The systemic risk buffer should be added to the toolkit, although its activation and level may still need further analysis.